2008
DOI: 10.1093/eurpub/ckn062
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for anabolic-androgenic steroid abuse among Jordanian collegiate students and athletes

Abstract: Abusing AAS is starting to become a public health concern that implies the need to implement educational programmes, which will educate and warn adolescents and mentors about the negative side effects of AAS abuse on the health of users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
46
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(69 citation statements)
references
References 23 publications
10
46
3
2
Order By: Relevance
“…A study held in Jordan (Middle East) analyzed the use of AAS among 503 university students and 154 bodybuilders through questionnaires. Out of the investigated individuals, it was observed that 4.2% of the university students and 26.0% of the athletes were current users 9 . in a scientific review on the use of AAS in Brazil, prevalence of the use of AAS ranged between 2.1 and 25.5%, according to the sample characteristics and the analyzed region.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…A study held in Jordan (Middle East) analyzed the use of AAS among 503 university students and 154 bodybuilders through questionnaires. Out of the investigated individuals, it was observed that 4.2% of the university students and 26.0% of the athletes were current users 9 . in a scientific review on the use of AAS in Brazil, prevalence of the use of AAS ranged between 2.1 and 25.5%, according to the sample characteristics and the analyzed region.…”
Section: Introductionmentioning
confidence: 94%
“…in Brazil, there are still few data about the indiscriminate use of AAS 6,[10][11][12] . it is observed that the amount of AAS has been increasing, despite the awareness of many collateral effects, already described in the literature [7][8][9][10][11] . However, it is evidenced that there are few studies about the use of AAS among physical education students and professors [13][14][15] .…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies in Jordan found that 26 % of bodybuilders reportedly used anabolic steroids [10]. The use of anabolic steroids among gym users in United Arab Emirates was estimated at 22 % [2] while AAS use among Iranian youths training to be bodybuilders was about 13 % [11].…”
Section: Introductionmentioning
confidence: 99%
“…The use of AAS is not a new issue for the sport, and the collective term steroid is officially used to denote illegitimate performance enhancement substances and methods among professional and amateur bodybuilders. AAS is mostly taken by athletes and adolescents to enhance performance and physical appearance (Tahtamouni et al, 2008;Amsterdam et al, 2010). The AAS are synthetic substances related to the male sex hormones which influence the growth of skeletal muscles and the development of male sexual characteristics (Lundholm et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it is said that the usage of steroids is not only found among bodybuilders who want to gain an advantage, but also among the public whose lifestyle purpose involves using doping substances. AAS violates sports ethics and may have serious implications for the physical and mental health of the bodybuilders, including cardiovascular conditions, renal complications, rhabdomyolysis, infectious complications from the injection technique used in self administration, tendon and ligament ruptures, thyroidal impairment, azoospermia, major mood disturbances and even increased premature mortality (Amsterdam et al, 2010;Tahtamouni et al, 2008).…”
Section: Introductionmentioning
confidence: 99%